Is the Combination of Sulfonylureas and Metformin Associated With an Increased Risk of Cardiovascular Disease or All-Cause Mortality? - Rao, Ajay D.; Kuhadiya, Nitesh; Reynolds, Kristi; Fonseca, Vivian A. (Diabetes care, 2008)
Is the Combination of Sulfonylureas and Metformin Associated With an Increased Risk of Cardiovascular Disease or All-Cause Mortality? A meta-analysis of observational studies Ajay D. Rao , MD 1 , Nitesh Kuhadiya , MBBS 2 , Kristi Reynolds , PHD, MPH 2 , 3 and Vivian A. Fonseca , MD 1 1 Department of Medicine, Tulane University School of Medicine, New Orleans, Louisiana 2 Department of Epidemiology, Tulane University School of Public Health and Tropical Medicine, New Orleans, Louisiana 3 Southern California Kaiser Permanente Medical Group, Pasadena, California Corresponding author: Vivian Fonseca, vfonsecaattulane.edu Abstract OBJECTIVE —Observational studies assessing the association of combination therapy of metformin and sulfonylurea on all-cause and/or cardiovascular mortality in type 2 diabetes have shown conflicting results. We therefore evaluated the effects of combination therapy of sulfonylureas and metformin on the risk of all-cause mortality and cardiovascular disease (CVD) among people with type 2 diabetes. RESEARCH DESIGN AND METHODS —A MEDLINE search (January 1966–July 2007) was conducted to identify observational studies that examined the association between combination therapy of sulfonylureas and metformin on risk of CVD or all-cause mortality. From 299 relevant reports, 9 were included in the meta-analysis. In these studies, combination therapy of metformin and sulfonylurea was assessed, the risk of CVD and/or mortality was reported, and adjusted relative risk (RR) or equivalent (hazard ratio and odds ratio) and corresponding variance or equivalent was reported. RESULTS —The pooled RRs (95% CIs) of outcomes for individuals with type 2 diabetes prescribed combination therapy of sulfonylureas and metformin were 1.19 (0.88–1.62) for all-cause mortality, 1.29 (0.73–2.27) for CVD mortality, and 1.43 (1.10–1.85) for a composite end point of CVD hospitalizations or mortality (fatal or nonfatal events). CONCLUSIONS —The combination therapy of metformin and sulfonylurea significantly increased the RR of the composite end point of cardiovascular hospitalization or mortality (fatal and nonfatal events) irrespective of the reference group (diet therapy, metformin monotherapy, or sulfonylurea monotherapy); however, there were no significant effects of this combination therapy on either CVD mortality or all-cause mortality alone. Footnotes Published ahead of print at http://care.diabetesjournals.org on 5 May 2008. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C Section 1734 solely to indicate this fact. Received February 7, 2008. Accepted April 29, 2008. DIABETES CARE